Assessing Coastal Plain Risk Indices for Subsurface Phosphorus Loss. Issue 6 (1st November 2017) - Shober, Amy L.; Buda, Anthony R.; Turner, Kathryn C.; Fiorellino, Nicole M.; Andres, A. Scott; McGrath, Joshua M.; Sims, J. Thomas
Abstract : Phosphorus (P) Index evaluations are critical to advancing nutrient management planning in the United States. However, most assessments until now have focused on the risks of P losses in surface runoff. In artificially drained agroecosystems of the Atlantic Coastal Plain, subsurface flow is the predominant mode of P transport, but its representation in most P Indices is often inadequate. We explored methods to evaluate the subsurface P risk routines of five P Indices from Delaware, Maryland (two), Virginia, and North Carolina using available water quality and soils datasets. Relationships between subsurface P risk scores and published dissolved P loads in leachate (Delaware, Maryland, and North Carolina) and ditch drainage (Maryland) were directionally correct and often statistically significant, yet the brevity of the observation periods (weeks to several years) and the limited number of sampling locations precluded a more robust assessment of each P Index. Given the paucity of measured P loss data, we then showed that soil water extractable P concentrations at depths corresponding with the seasonal high water table (WEPWT ) could serve as a realistic proxy for subsurface P losses in ditch drainage. The associations between WEPWT and subsurface P risk ratings reasonably mirrored those obtained with sparser water quality data. As such, WEPWT is seen as a valuable metric that offers interim insight into the directionality of subsurface P risk scores when water quality data are inaccessible. In the long term, improved monitoring and modeling of subsurface P losses clearly should enhance the rigor of future P Index appraisals. Core Ideas: We evaluated subsurface P routines of five P Indices in artificially drained soils. Subsurface P ratings mostly accorded with P loads in leachate and ditch drainage. Water extractable P at the seasonal high water table was a proxy for ditch P loss. Useful P Index predictions hinged on accurate depictions of subsurface water flux. Increased monitoring and modeling of subsurface P loss is needed to test P Indices.